Мовні експерименти Павла Загребельного - Голікова, Н. (Культура слова, 2019)
Досліджено семантичну структуру лексеми «стовп» у мові художньої прози П. Загребельного, виявлено специфіку її символьних значень. Проаналізовано лінгвостилістичні функції полісеманта в історичних романах і творах про сучасність письменника. Схарактеризовано риторичні фігури, що в романі «Стовпо-творіння» П. Загребельного є наслідком мовних експериментів зі словом «стовп». Визначено лексико-тематичні лінії з домінантою «стовп» у текстово-польовій структурі твору. Індивідуально-авторські фігури мови комплексно проаналізовано в межах лінгвостилістики, неології, літературної ономастики. The article researches semantic structure of the “pillar” tokens in the vertical context of fictionof P. Zagrebelnyi. The structure of symbolic meanings of polysemant, its linguostylistic functions in historical novels and works about the writer’s present time are analyzed. It is characterized by rhetorical figures that in the novel “Stovpo-tvorinnia” by P. Zagrebelnyi is the result of language experiments with the word “pillar”. Identified lexical-thematic lines with the dominant “pillar” in the text-field structure of the work, clarified their semantic-derivative specificity. Individualauthor figures of language are comprehensively analyzed within the framework of linguistics, neology, and literary onomastics.